2004
DOI: 10.1111/j.1365-3164.2004.00414_4.x
|View full text |Cite
|
Sign up to set email alerts
|

P‐4 
Canine recurrent pyoderma: a multicenter prospective study

Abstract: Skin physiology in cats has received little attention. The aim of this study was to evaluate the long-term influence of sex, time and the level of dietary fat and energy on the dynamics and qualities of the hair coat. Twenty-four European short-haired laboratory cats were followed over a 1-year period. They were divided into eight groups of three, according to: sex (12 males and 12 females), sexual status (intact or neutered) and diets [(high energy 4300 kcal/kg as fed, 21% fat) vs. (moderate energy 3500 kcal/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…6 Another study only found one underlying disease in 28 of the 30 dogs evaluated. 7 Concurrent environmentally induced atopic dermatitis and cutaneous adverse food reactions occurred slightly more oten in this study than reported by Picco et al 8 and Hillier and Griin. 9 As the latter authors suggest, such results have to be interpreted with caution.…”
Section: Discussioncontrasting
confidence: 41%
“…6 Another study only found one underlying disease in 28 of the 30 dogs evaluated. 7 Concurrent environmentally induced atopic dermatitis and cutaneous adverse food reactions occurred slightly more oten in this study than reported by Picco et al 8 and Hillier and Griin. 9 As the latter authors suggest, such results have to be interpreted with caution.…”
Section: Discussioncontrasting
confidence: 41%
“…Most cases of deep pyoderma in the dog (97%) are caused by infection with Staphylococcus pseudintermedius . Suggested first‐line empirical choices to treat acute deep pyoderma are clindamycin, amoxicillin‐clavulanate or first‐generation cephalosporins, but a recent systematic review of the literature found good quality evidence only for use of amoxicillin‐clavulanate .…”
Section: Discussionmentioning
confidence: 99%
“…Dogs with a history of more than three episodes of skin infections in the past one year were included in the study as also done by Bensignor and Germain [4]. The dogs were thoroughly examined clinically for the presence of macroscopic ectoparasites.…”
Section: Methodsmentioning
confidence: 99%
“…The present investigation was carried out on the dogs referred to C.V.Sc, S.V.V.U., Tirupati, Andhra Pradesh, India, and dogs presented at the major veterinary hospitals around Tirupati. Dogs with a history of more than three episodes of skin infections in the past one year were included in the study as also done by Bensignor and Germain [ 4 ]. The dogs were thoroughly examined clinically for the presence of macroscopic ectoparasites.…”
Section: Methodsmentioning
confidence: 99%